A Splenic Infarction Related to Parainfluenza Infection in a Patient with AML: Lessons for COVID-19: Viral infection and splenic infarction - Sahu, Kamal Kant; E. Vogt, Bennett; Shanahan, Lindsey; Cerny, Jan (Acta Biomedica Atenei Parmensis, 2021)
NA